Occurrence of multidrug resistant e.coli and campylobacter in chicken and chicken meat and their associated risk factors - Jalo, Muhammad Ibrahim (2015)
Antibiotic usage is an important factor that have been widely reported to bring about the emergence and spread of antibiotic resistant microorganisms in both animal and human health. Chickens may be infected with antibiotic resistant Campylobacter and E.coli which may be resistant to one or more antibiotics. There is an alarming increase of multidrug resistance among bacterial pathogens affecting human and animal populations globally. There is limited data on the occurrence of multidrug resistance (MDR) E. coli and Campylobacter in poultry and poultry meat in Malaysia. This study was aimed at investigating the occurrence of multidrug resistant E. coli and Campylobacter in chicken and chicken meat and their associated risk factors. The specific objectives were: to determine the occurrence of E.coli and Campylobacter in chickens and farm environment and chicken meat retailed in the markets and their associated risk factors and to determine the antibiotic resistance and MDR profiles of the isolates from chicken and chicken meat. Two hundred and ten (210) samples were collected from five farms and seventy (70) samples from seven markets. Five (5) farms were visited three (3) times each during the study period. The first visit was to sample chicken at market age (35-42 days) prior to harvesting (considered as first population) and farm environment (which is included water, feed, flies and chicken house floor). The second visit was to sample farm environment at two (2) weeks after the chicken farms were emptied (all chicken were sold), cleaned and disinfected and the third visit was carried out on a new batch of chickens at market age also prior to harvesting (as second population) and the environment. In each farm, thirty (30) cloacal swab samples and twelve (12) environmental samples which consisted of three (3) samples each of water from the drinker, feed from the feeder, chicken house floor and pooled samples of flies each consisting 5-7 per pooled sample were collected (3). Chicken meat which consisted of breast, thigh and wings including the skin were randomly chosen from stalls in each market. The number of stalls visited in seven markets varied from 4 to 10 per market depending on the number of poultry meat retailers in that market. Cutting boards and weighing scales were also sampled. Fifty five point seven percent (60.0% and 51.3%) of the chickens in the first and second population were colonized with Campylobacter. The proportion of Campylobacter isolated from environmental samples in the first and third visits was 7.5% (1.7% and 13.3%). Only one water sample (6.7%) was positive (first visit) and two (13.3%) in the third visit. Flies were found positive for Campylobacter only in the third visit (33.3%). Among the chicken house floor samples, only one was positive (6.7%). All feed samples were negative (0%). The most frequently isolated species was C. jejuni at 74.9% (82.2% and 67.5%), followed by C. coli 25.2% (17.8% and 32.5%). At the markets, the occurrence of Campylobacter was 20.0% for chicken meat, and 5.7% for weighing scales and cutting boards. The species identified were 78.6%, 17.9% and 3.6% for C.jejuni, C.coli and C.upsaliensis respectively. The occurrence of E.coli in chickens is 53.0% (56.0% and 50.0%). Similarly, the occurrence of E.coli in environmental samples at first and third visits were 33.4% (26.7%, 0% and 40.0%). Among the environmental samples, the isolation of E.coli in feed was 16.7%, floor 40.0%, water 20.0% and flies 56.7%. The occurrence of E.coli in chicken meat at markets was 45.0%. In the farms, the occurrence of the Campylobacter and E.coli in the first and second population were almost similar; this was probably due to the farm practices were similar and the biosecurity measures practised in the farm may not be sufficient. The presence of flies and birds around the farm and/or the use of contaminated water may transfer these bacteria to the chickens or the workers brought them into the chicken houses from the farm environment. At the markets,cross contamination was a possible factor because during meat handling and cutting,the surfaces of poultry carcasses could become contaminated with Campylobacter and E.coli from the intestinal content due to accidental rupture of the gut or from contaminated equipment or water. The absence of Campylobacter in feed samples may probably be due to poor resistance of Campylobacter to atmospheric condition and other environmental pressures during storage that would have converted to viable-but-non-culturable (VBNC) form. It was reported that most flocks were negative until two (2) weeks of age, and once Campylobacter colonized a broiler flock, the spread is very rapid and up to 100% of birds within a flock can become colonized within three days. The antibiotic resistance of these Campylobacter (n=208) and E.coli (n=269) isolates was done using disc diffusion method against 12 different antibiotics. Campylobacter isolates from first and second population showed high resistance to penicillins at 75.5% (74.4% and 76.6%) and the least resistance was to amoxycillin_clavulanic acid at 33.7% (32.2% and 35.1%). Sixty two point five percent (62.5%) Campylobacter isolated from chicken meat was resistant to ampicillin and the least was to treptomycin, 3.1%. E.coli isolated from chicken in first population showed high resistance to penicillin, erythromycin, ampicillin and tetracycline at 98.8%, 96.4%, 94.0% and 92.8% respectively and the least resistance was to amoxycillin_clavulanic at 22.9%. Those isolated from the second population were 100% resistant to erythromycin and tetracycline and the least resistance was to cefotaxime at 20.0%. In chicken meat, the highest resistance was to erythromycin and penicillins at 100% each and the least was to gentamicin at 40%. The high resistance may likely be as a result of imprudent use of these agents for growth promotion and for prophylactic purposes at farm level. Multidrug resistance (MDR) (resistance to 3 or more classes of antibiotics) was high in Campylobacter isolated in chicken farms, at 87.5%, chicken meat 71.9%, while in E.coli it was 99.5% for chicken, and for chicken meat was 100%. The most common multidrug resistance profile for Campylobacter isolates in chicken was to 7 (EPNaCtxSCipAmp) and 10 (EPNaCipTeAmcSxtCnEnrAmp) classes of antibiotics at 13.2% each in the first population. In the second population, the common MDR pattern was to 9 (EPNaCtxSCipAmcEnrAmp) classes at 12.9%. In chicken meat it was to 4 (TeAmcEnrAmp) and 5 (EPTeCtxAmp) classes at 15.6% each. The most common MDR profile for E. coli was to 9 (EPNaSCipTeAmcSxtAmp) and 10(EPNaSCipTeAmcSxtEnrAmp) antibiotic classes at 16.0% each in the first population and in the second population, the most common profile was to 8 (EPNaSCipTeAmcSxtEnrAmp) classes at 19.2%. It was to 8 (EPNaSCipTeEnrAmp) classes of antibiotics at 21.4% in chicken meat. The findings suggested the possible persistence of the resistant organisms in the farm environment even after cleaning and disinfection of the chicken houses. Flies may had play a role in introducing the resistant bacteria to the chicken farm and environment. Imprudent use of antibiotics as growth promoters or for therapeutic purposes not administered professionally could lead to development of resistance by these bacteria. However, health records were not available in the farms and information on antibiotics used could not be obtained making it impossible to make sound deduction except to make assumptions. Risk factors that were significantly (p<0.05) associated with Campylobacter contamination in chickens meat included; no working attire (OR 2.7, CI 1.144-6.374,p=0.033), fair and poor usage of protective equipment (OR 12.6, CI 1.186-133.899,p=0.036) and (OR 38.50, CI 2.915-508.463, p=0.006) respectively, poor stall hygiene (OR 44.00, CI 2.193-882.66, p=0.013) and use of wood counter surface (OR 6.1, CI 1.198-31.164, p=0.029). The relevant but not significant factor was poor working hygiene (OR 5.250, CI 0.988-27.895, p=0.05). This study identified five risk factors for Campylobacter contamination that, if taken together, might account for most sporadic cases. The presence of high MDR Campylobacter and E.coli species could compromise treatment in humans and in particular, if the bacteria is resistant to the drugs of choice and alternative drugs for treatment and therefore poses a significant public health risk. Certainly, at farm level, the prevalence of MDR Campylobacter and E.coli in broiler flocks should be monitored. From this study it was observed that there is a need to stress the awareness among farmers to observe good hygienic practices and prudent use of antibiotics to reduce the menace of antibiotic resistance.